9x+18=26-3X

Simple and best practice solution for 9x+18=26-3X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+18=26-3X equation:


Simplifying
9x + 18 = 26 + -3X

Reorder the terms:
18 + 9x = 26 + -3X

Solving
18 + 9x = 26 + -3X

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 9x = 26 + -18 + -3X

Combine like terms: 18 + -18 = 0
0 + 9x = 26 + -18 + -3X
9x = 26 + -18 + -3X

Combine like terms: 26 + -18 = 8
9x = 8 + -3X

Divide each side by '9'.
x = 0.8888888889 + -0.3333333333X

Simplifying
x = 0.8888888889 + -0.3333333333X

See similar equations:

| 4x+(144+x)=180 | | 4-c+2=5c+1 | | 2a(a-5)+(a-5)= | | k^2+4=16 | | (3x-6)+10=10+4x | | 6=48*oz | | .4y-4=.33y | | -x^2-8x-9=0 | | e*80=2 | | 5=2x | | m*7=13 | | 16=w*4 | | c*9=6 | | -7-4r=-3(-7-8r) | | 7(x+2)=8-5(x-7) | | 8l+8-l=9-8 | | 3x-2x+10=10+5x-40 | | 4x+2=8-2x | | C^3-216=y | | 3(-7-6x)-8=37+4x | | 5+2x=7(x+2)-6(x-2) | | x^2+21x+59=0 | | -(3-m)=-(4m+3) | | 100/566=1/9 | | -(x+1)+2=2x+1-3x | | 3(x+2)=9x+3-6x+3 | | 900/566= | | 10x-9=21+2x+3x | | -7a-(-2b)= | | k*36=8 | | -2(t-5)+9t=3t-4 | | 4(x-2)=8x-6-4x |

Equations solver categories